Determinants of Capital Adequacy Ratio Through Size, Liquidity, Credit Risk and Operational Efficiency in Sharia Commercial Banks in Indonesia - Havid Risyanto (Jurnal Ilmiah Ekonomi Islam, 2021)
This research aims to determine whether the variable Size, Liquidity, Credit Risk, Operational Efficiency is a determinant of the Capital Adequacy Ratio in Islamic Commercial Banks in Indonesia using Panel Data Regression Analysis and Fixed Effect Model as the best model. The results obtained in this research indicate that the variables Size, Liquidity, Credit Risk, and Operational Efficiency simultaneously have a positive and significant effect on the Capital Adequacy Ratio in Islamic Commercial Banks for the 2016-2019 Period. While partially the results obtained that the variables Size, Liquidity, and Credit Risk do not have a significant effect and have a positive relationship to the Capital Adequacy Ratio. While the Operational Efficiency variable has a significant influence and has a negative relationship with the Capital Adequacy Ratio in Islamic Commercial Banks for the 2016-2019 Period. And in this research shows the ability of the independent variable in explaining the dependent variable is 80.9218%.